À nouveau travail, formations nouvelles - Lapointe, Paul-André (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "À nouveau travail, formations nouvelles," by Collette Bernier and Anne Filion.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z